Oczywistość - Chojecki, Andrzej (Er(r)go. Teoria - Literatura - Kultura, 2009)
The Evident Abstract in English In "The Evident" Andrzej Chojecki sets out to illuminate the eponymous category through recourse to its etymology which demonstrates that the evident is a matter of visual perception in the first place. His project of demarcating the semantic boundaries of the category prompts him to discuss Aristotle"s views in the light of their subjectivisation of the evident: what is evident for one person, does not have to be evident for another. As the absolutely primary determinant of the evident. We must recognise God, which is conveyed by means of the formula Ego sum qui sum (I am that I am). In what follows Chojecki refers to the views of such philosophers and writers as Hegel, Heidegger. Husserl, Schopenhauer, Shestov and Nietzsche in the context of the relationships or encounters of the category of the evident with the categories of truth, certainty. understanding, identity. perceptibility, representation. Finally, he elaborates on the association of the evident with the Cartesian "ergo." .